Pengaruh Kualitas Pelayanan, Kepuasan Dan Kepercayaan Pasien Terhadap Behavioural Intention Pada Klinik Gigi Dentes Provinsi DIY - Fransius Awaldo Damanik; Abdur Rochman Tri Setyawan (Universitas Hamzanwadi, 2022)
This study aims to determine the effect of service quality, satisfaction and patient trust on behavioral intentions at Dentes Dental Clinic in Yogyakarta Province. Probability sampling method in this study there are 120 respondents who are Dentes Dental Clinic patients in DIY Province with an age range of 18-40 years. Primary data was collected using a questionnaire method that has been tested for validity and reliability. Based on the results of data testing using the classical assumption test and multiple regression analysis, it was found that: service quality, patient satisfaction, and trust had a positive and significant effect on behavioural intentions. Service quality variable on patient satisfaction and the influence of the patient satisfaction variable on trust also has a positive and significant effect. The regression coefficient value of the influence of service quality variables on behavioral intention is 0.391. The regression coefficient value of the effect of patient satisfaction on behavioral intention is 0.097. The value of the regression coefficient of the influence of the trust variable on behavioral intention is 0.193. The regression coefficient value of the influence of service quality variables on behavioral intention is 0.337. The regression coefficient value of the effect of patient satisfaction on trust is 0.048.